Exploring attentional biases towards facial expressions of pain in men and women. (4th June 2018) - Keogh, E.; Cheng, F.; Wang, S.
Abstract: Background: Interpersonal factors may help explain why men and women differ in their perception and expression of pain. Whilst the focus is often on the person in pain, how observers respond to those in pain is important. This study explored whether male–female differences exist in the way observers attend to expressions of pain in others. Methods: Fifty‐three adults (26 females) completed a visual dot‐probe task, to measure selective attentional biases to facial expressions of pain and fear. Expression pairs (e.g. pain/neutral) were displayed by either the same male or female actor, and in two different viewing duration conditions: 150 and 1250 ms. Dot‐probes appeared in either a congruent or incongruent location to the target expression. Results: No evidence was found for sex‐related attentional biases towards pain or fear. However, when examining congruency and incongruency indexes separately, differences emerged. The congruency index analysis indicated that in the 150‐ms presentation condition, both men and women were slower during congruent female pain/neutral trials when compared to neutral/neutral trials, and relatively faster at responding during congruent male pain/neutral trials. Conclusions: There is utility in exploring the attentional processes involved in the decoding of pain‐related expressions to understand the influence of sex and gender differences in pain. Although male–female differences were found, this was most clearly related to the actor. Our results point to an early attentional mechanism that orients attention away from female expressions of pain. Future consideration of sex‐ and gender‐related contextual factors in attentional processing is warranted. Significance: Sex‐related factors seem to affect how observers view the pain of others. Our results point to an early attentional mechanism that orients the attention of observers away from female expressions of pain.